2020
DOI: 10.1007/s12015-020-10005-w
|View full text |Cite
|
Sign up to set email alerts
|

Nlrp3 Inflammasome Signaling Regulates the Homing and Engraftment of Hematopoietic Stem Cells (HSPCs) by Enhancing Incorporation of CXCR4 Receptor into Membrane Lipid Rafts

Abstract: Fast and efficient homing and engraftment of hematopoietic stem progenitor cells (HSPCs) is crucial for positive clinical outcomes from transplantation. We found that this process depends on activation of the Nlrp3 inflammasome, both in the HSPCs to be transplanted and in the cells in the recipient bone marrow (BM) microenvironment. For the first time we provide evidence that functional deficiency in the Nlrp3 inflammasome in transplanted cells or in the host microenvironment leads to defective homing and engr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
78
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(82 citation statements)
references
References 67 publications
(103 reference statements)
4
78
0
Order By: Relevance
“…A series of studies by the Ratajczak group indicated a novel mechanism by which the NLRP3 inflammasome plays dual roles in the regulation of HSPC migration toward BM chemoattractants and also responds to myeloablative irradiation of the BM microenvironment to facilitate the homing and engraftment of transplanted cells [ 94 ]. The researchers first illustrated that the MBL-initiated ComC and coagulation cascade (CoaC) are involved in triggering the mobilization of HSPCs [ 95 ].…”
Section: Extracellular Signals Activate the Inflammasome Through Pmentioning
confidence: 99%
See 4 more Smart Citations
“…A series of studies by the Ratajczak group indicated a novel mechanism by which the NLRP3 inflammasome plays dual roles in the regulation of HSPC migration toward BM chemoattractants and also responds to myeloablative irradiation of the BM microenvironment to facilitate the homing and engraftment of transplanted cells [ 94 ]. The researchers first illustrated that the MBL-initiated ComC and coagulation cascade (CoaC) are involved in triggering the mobilization of HSPCs [ 95 ].…”
Section: Extracellular Signals Activate the Inflammasome Through Pmentioning
confidence: 99%
“…The researchers then proposed that the ATP-induced NLRP3 inflammasome acts as a neutralizer that connects purinergic signaling with the activation of the ComC, which is required for the egress of HSPCs from the BM into the PB [ 98 ]. In fact, proper NLRP3 inflammasome expression in HSPCs is also required for the migration of HSPCs in response to BM-expressed homing factors [ 94 ]. Activation of the NLRP3 inflammasome in HSPCs promotes the incorporation of CXCR4 into membrane lipid rafts, which enhances the release of eATP in an autocrine/paracrine manner to facilitate the migration of HSPCs in response to an SDF-1 gradient [ 94 ].…”
Section: Extracellular Signals Activate the Inflammasome Through Pmentioning
confidence: 99%
See 3 more Smart Citations